1976
DOI: 10.1136/adc.51.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Continuous postive airways pressure treatment by a face chamber in idiopathic respiratory distress syndrome.

Abstract: . Continuous positive airways pressure treatment by a face chamber in idiopathic respiratory distress syndrome. During a 3-year period 45 infants with idiopathic respiratory distress syndrome (IRDS) requiring ventilatory support were treated in the neonatal unit. Continuous positive airways pressure (CPAP) via the face chamber was applied as initial therapy in 39 infants and during weaning from initial intermittent positive pressure ventilation (IPPV) treatment in 5 infants, whereas 1 infant received IPPV only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…In a previous study [3] we found that treatment with the CPAP-f.c. technique was efficient in most cases of HMD (see Table 5).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a previous study [3] we found that treatment with the CPAP-f.c. technique was efficient in most cases of HMD (see Table 5).…”
Section: Discussionmentioning
confidence: 83%
“…The face chamber with its supporting intensive care crib, gas mixer and humidifier (Fc 100, Siemens-Elema AB, Solna, Sweden) (Fig. 1) has been presented previously [3]. When HMD had been diagnosed according to the criteria shown in Table 1, CPAP-f.c.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore we used tracheal intubation. Possibly these difficulties can be avoided using a facechamber as recently described (2). The children did not show laryngeal damage.…”
Section: Discussionmentioning
confidence: 85%
“…Device. The face chamber device for CPAP treatment is non-invasive; it enables truly continuous positive airway pressure to be maintained, while leaving the airways, neck and chest unrestricted (9,17). Our modification of the device makes it possible to study ventilation and breathing patterns without interference of treatment, addition of dead space, addition of resistance, manipulation of the infant or sensory stimulation of the face (5,18,19).…”
Section: Discussionmentioning
confidence: 99%